Do forests help rural households adapt to climate variability: evidence from southern Malawi - Fisher, M.; Chaudhury, M.; McCusker, B. (2010)
Data from rural Malawi are used to assess the role of forests in rural household adaptation to climate variability, and to examine implications for adaptation to future climate change. Although forests do not currently play a role in anticipatory adaptation by rural households, they do appear important for reactive coping: providing food during shortages, and a source of cash for coping with weather-related crop failure. We find households most reliant on forests have low income per person, are located close to forest, and are headed by individuals who are older, more risk averse, and less educated than their cohorts